Numerical modeling of dynamic indignation plane flight by un linear modification of aerodynamics characteristics - Балакірев, А. Н.; Удовенко, В. А.; Швець, О. В. (Proceedings of National Aviation University (archive), 2003)
Calculation of indignation longitudinal motion of the light plane had showed. There is reason to use nonlinear modification aerodynamic performances instead off linear model of aerodynamic performances. The graphic results are presented